Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja di PT. KAI Semarang Indonesia - Kusni Ingsih; Puji Rahman; Agus Prayitno (Universitas Musamus,Merauke,Papua, 2021)
The purpose of this study was to analyze the influence of organizational culture, organizational commitment on job satisfaction and its impact on employee performance at PT. KAI DAOP IV Semarang Indonesia. The population in this study were permanent employees at PT. KAI Daop IV Semarang as many as 215 people. The sampling technique in this study used purposive sampling, namely sampling based on criteria or considerations, including: permanent employees at PT. KAI Daop IV Semarang, which has worked for at least 2 years, so that 103 samples were obtained. The data analysis method used is multiple linear regression. The results showed that there was a positive and significant influence of organizational culture and organizational commitment on job satisfaction. Other results show that there is a positive and significant effect of organizational culture, organizational commitment and job satisfaction on employee performance. The results of the mediation effect test showed that job satisfaction was able to mediate the influence of organizational culture on employee performance, while job satisfaction was unable to mediate the effect of organizational commitment on employee performance.